AN ERROR ANALYSIS ON CONSTRUCTING WH-QUESTION MADE BY THE SECOND YEAR STUDENT OF SMA MUHAMMADIYAH 2 KLATEN IN 2006 / 2007 ACADEMIC YEAR - HASTUTIK , DUWI (2007)
This research is conducted to achieve some objectives, they are to find out: (1) the types of errors made by the students in constructing WH-Questions based on surface strategy taxonomy; (2) the frequency of each type of errors; and (3) the dominant type of errors made by the students. The method used in this study is descriptive method. The research was conducted on September 19th , 2006. The subject of the s tudy is the second year student of SMA Muhammadiyah 2 Klaten. The cluster sampling is used to get one class consisting 34 students out of five classes as the sample. The data analysis was started by collecting the data, identifying errors, classifying errors, and then counting the error percentage to find out the frequency of errors. Thirty items of essay test in 60 minutes were used as the instrument in collecting the data. The result of the study shows that there are 227 errors made by the students in constructing WH-Questions. Those errors are analyzed b ased on the surface strategy taxonomy, they are omission (72 or 31,72%), addition (50 or 22,03%), misformation (94 or 41,41%), and misordering (11 or 4,84%). Concerning with the percentage of errors, misformation becomes the dominant type of errors. It means that most of the students still have difficulties in mastering structure, especially constructing WH-Questions.